2021
DOI: 10.3233/prm-190635
|View full text |Cite
|
Sign up to set email alerts
|

Immersive virtual reality in children with upper limb injuries: Findings from a feasibility study

Abstract: PURPOSE: Children who sustain Upper Limb Injuries (ULIs), including fractures and burns, may undergo intensive rehabilitation. The discomfort of therapy can reduce their compliance, limit their range of motion (ROM) and lead to chronic pain. Virtual Reality (VR) interventions have been found to reduce anticipated and procedural pain. This feasibility study aimed to explore perceptions and impacts of a custom-made, fully immersive Head-Mounted Display VR (HMD-VR) experience within a United Kingdom (UK) National… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 48 publications
3
15
0
Order By: Relevance
“…The magnitude of pain reduction was sustained with repeated VR use over different physiotherapy sessions (Hoffman et al, 2001; Sharar et al, 2007). Consistent with other findings, Hoffman et al (2014) and Phelan et al (2021) found that children reported less pain with VR during physiotherapy.…”
Section: Resultssupporting
confidence: 85%
See 3 more Smart Citations
“…The magnitude of pain reduction was sustained with repeated VR use over different physiotherapy sessions (Hoffman et al, 2001; Sharar et al, 2007). Consistent with other findings, Hoffman et al (2014) and Phelan et al (2021) found that children reported less pain with VR during physiotherapy.…”
Section: Resultssupporting
confidence: 85%
“…All randomised trials reported that VR distraction led to a significant reduction for pain intensity (Ali et al, 2021;Schmitt et al, 2011;Sharar et al, 2007), pain unpleasantness (Schmitt et al, 2011;Sharar et al, 2007;Soltani et al, 2018) and time spent thinking about pain (Schmitt et al, 2011;Sharar et al, 2007;Soltani et al, 2018) magnitude of pain reduction was sustained with repeated VR use over different physiotherapy sessions (Hoffman et al, 2001;Sharar et al, 2007). Consistent with other findings, Hoffman et al (2014) and Phelan et al (2021) found that children reported less pain with VR during physiotherapy.…”
Section: Virtual Reality Adjunct To Standard Analgesia Improves Pain ...supporting
confidence: 65%
See 2 more Smart Citations
“…School-age children are the most vigorous period of the development of various physiological functions in their lives [ 10 ]. There is a big difference in the anatomy, injury mechanism and healing characteristics of adults [ 11 ]. Fracture injuries in children are often accompanied by bone damage.…”
Section: Introductionmentioning
confidence: 99%